Azo–Hydrazone Tautomerism in Organometallic Complexes Triggered by a -Re(Co)3(L) Core: A Spectroscopic and Theoretical Study - Aspee-Lamas, A; Arancibia-Miranda, N; Arancibia-Miranda, N; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Gomez-San Martin, A; Gomez-San Martin, A; Aravena-Ponce, D; Aravena-Ponce, D; Maldonado-Hernandez, T; Maldonado-Hernandez, T; Flores-Vergara, E; et al. (Elsevier Ltd, 2022)
The spectroscopic properties and tautomeric behavior of five novel Rhenium (I) tricarbonyl complexes bearing an azo ligand are presented. The organic ligand is stable in solution as the hydrazone tautomer. It remains as hydrazone in different medium conditions (solvent, concentration, pH, etc.) without the formation of detectable amounts of the azo tautomer. However, the complexation of this ligand to the strong electron-withdrawing fragment -Re(CO)3X (X = Cl−, Br−) causes tautomerism to appear in the organic moiety. Two well-defined regions in the electronic spectra for both tautomers were observed, allowing the azo/enol-keto/hydrazone equilibrium to be followed. TD-DFT calculations indicate that for the keto/hydrazone form, the main absorption band is attributed to an IL transition. In contrast, the azo/enol species shows a major contribution of the 1MLCT (dπ(Re) → dπ*(NN)) transition. The tautomeric equilibrium is easily shifted using solvents with different dielectric constant and hydrogen bond donor/acceptor (HBD/HBA) abilities. Also, the tautomerization process is deeply influenced by the electronic properties of the axial ligand. Therefore, this behavior represents a different strategy for the design of novel materials with optical properties. Furthermore, tautomerism is affected by the concentration of complexes and the presence of water in solvents. The acid-base behavior of these compounds in a 50% v/v ethanol-buffer system showed that the azo/enol tautomer is stabilized in acidic media. At the same time, an increase of pH promotes tautomerization toward the keto/hydrazone, followed by forming the anionic form at pH > 8. © 2021 Elsevier Ltd